3D visualization of fluid flow behaviors during methane hydrate extraction by hot water injection. (1st December 2019) - Yu, Tao; Guan, Guoqing; Abudula, Abuliti; Wang, Dayong
Abstract: Based on the geological conditions in the Shenhu Area of the South China Sea, a 3D methane hydrate reservoir model was built in this study. Numerical simulations of methane hydrate extraction using the method of horizontal wells in conjunction with hot water injection were conducted, and the fluid flow behaviors of gas and hot water were clearly revealed through 3D visualization of the physical properties, such as pressure, temperature, hydrate saturation, and gas saturation in the reservoir. In addition, the effects of reservoir properties on the production and fluid flow behaviors were investigated based on 3D analysis. The simulation results showed that, (1) high reservoir permeability was conducive to gas-liquid two-phase flow as well as pressure propagation and heat transfer in the reservoir, which was favorable for methane hydrate extraction by hot water injection; (2) permeability anisotropy could contribute to the reduction of water production from the reservoir, but also had a negative impact on the gas production process; and (3) high porosity was beneficial to gas recovery enhancement in the methane hydrate reservoir, but the effect on the fluid flow behaviors was not quite clear. Highlights: A 3D model was built for methane hydrate reservoir under real geological conditions. Horizontal wells with hot water injection were used for methane hydrate extraction. High permeability was favorable for hydrate extraction by hot water injection. Permeability anisotropy had a negative impact on the gas production process. High porosity was beneficial to gas recovery enhancement in hydrate reservoir.